Hubungan Keterlibatan Orang Tua dalam Belajar dengan Prestasi Belajar Matematika Kelas IV SD - adnan adnan; Andi St. Fatimah; Muh. Idris Jafar; muhammad amin (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
In this study, students experienced difficulties in learning mathematics which caused students to get low learning achievement anda the lack of parental involvement in the student learning process, this was due to the working conditions of parents, parents who were busy with work would be less involved in the students learning process.The results showed that there was a significant relationship between parental involvement in learning and mathematics learning achievement for grade IV SD Cluster I with t count (33.8) greater (>) t table (1.66320) which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the involvement of parents in learning can affect students' mathematics learning achievement. So, the better the involvement of parents in student learning, the better the mathematics learning achievement obtained by students. From these conclusions, the impact resulting from this study is known that parental involvement in good student learning will improve students' mathematics learning achievement.